1980
DOI: 10.2172/5200841
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for assessing the technical, environmental, and engineering feasibility of subseabed disposal

Abstract: V.i: s report presents r ve 1 onnent ii f the V. S. posal ef both hiah-Iev through joint efforts Isolation, the Sandia M in the ie str.i'.w a\,<. 'ianage^ient t":hn \ line nib •- ..-" a bo.'. [)i sposa 1 Prop rare i SOP ^ for '1 waste and spent fuel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The 1973 SDP "review strategy," shown in Figure 3 Campbell et al (1978) for the NRC and shown here in Figure 4, are primarily outlines of information flow or modeling strategy. The 1979 SDP "research approach" illustration shown at the bottom of Figure 3 (Anderson 1979, Anderson, Boyer, et al 1980, SNL Seabed Programs Division 1980 may be the earliest process-oriented depiction of the steps in a PA methodology. This illustration represented the process of developing, exercising, evaluating, and iterating component models, rather than the overall methodology.…”
Section: Evolution and Adaptation In The Snl Pa Methodologymentioning
confidence: 99%
“…The 1973 SDP "review strategy," shown in Figure 3 Campbell et al (1978) for the NRC and shown here in Figure 4, are primarily outlines of information flow or modeling strategy. The 1979 SDP "research approach" illustration shown at the bottom of Figure 3 (Anderson 1979, Anderson, Boyer, et al 1980, SNL Seabed Programs Division 1980 may be the earliest process-oriented depiction of the steps in a PA methodology. This illustration represented the process of developing, exercising, evaluating, and iterating component models, rather than the overall methodology.…”
Section: Evolution and Adaptation In The Snl Pa Methodologymentioning
confidence: 99%